Outdoor Learning Model by Utilizing Mount Penanggungan Cultural Heritage to Realize Education for Sustainable Development - Nuansa Bayu Segara; Agus Suprijono; Muhammad Ilyas Marzuqi (Universitas Pendidikan Ganesha, 2023)
The cultural heritage of Gunung Penanggungan has the potential to become a space for education for sustainable development. But it has not been optimally utilized by formal schools. This study aims to construct a learning model that can contribute to realizing the SDGs through education for sustainable development by utilizing the potential that exists in Mount Penanggungan. Design-based research is used in the development of this outdoor learning model. There are three stages of development: 1) analysis and exploration; 2) design and construction; and 3) evaluation and reflection. The subject of this study was the development of a one-day outdoor learning model involving two experts for qualitative product validation. Research data collection methods are adjusted to the research objectives, including: 1) literature studies, journals, proceedings, and relevant research books; 2) expert review; and 3) a validation sheet of the learning model draft.The data analysis used in this study is a qualitative-verifiable data analysis strategy. The results of this study show the components of the outdoor learning model, which consist of: 1) impact; 2) syntax; 3) the role of the teacher; 4) a support system; and 5) the principles of learning, have been worth testing. The outdoor learning model developed is considered to be in conformity with the objectives of ESD. School support, teacher competence and technical preparation are key to successful learning. The advantage of this model lies in the process of exploration, collaboration and reflection carried out directly in an outdoor class.